Mixed Connective Tissue Disease With Retroperitoneal Fibrosis: A Rare Occurrence - Aditya DHANAWAT,; Partisha GUPTA,; Prasanta PADHAN, (Archives of Rheumatology, 2020)
Mixed connective tissue disease (MCTD) is an autoimmune condition characterized by mixed clinical features of connective tissue diseases like systemic lupus erythematosus, polymyositis or systemic sclerosis with high titers of anti-U1 small nuclear ribonucleoprotein. Interstitial lung disease is a frequent manifestation of MCTD. Retroperitoneal fibrosis (RPF) is a rare fibro-inflammatory process involving the retroperitoneum. Majority of the cases are idiopathic and the rest are secondary to malignancies, infections or drugs. In this article, we describe a rare occurrence of RPF with MCTD.